Pendampingan Mahasiswa pada Program PLP di SMAN 7 Mataram: Penguatan Kompetensi Persiapan Mengajar Mahasiswa - R. Rahmawati; Syarifa Wahudah Al Idrus; Putri Santi; Della Puspita Amanda (Lembaga Yasin AlSys, 2026)
Although the School Field Introduction Program (PLP) serves as a strategic vehicle for prospective teacher students to integrate learning theory with practice in partner schools, directed mentoring is still needed so that students’ pedagogical readiness can develop optimally. This article aims to describe PLP student mentoring activities at SMAN 7 Mataram in strengthening abilities in three main domains, namely teaching preparation, guided learning, and independent learning. The mentoring activities were carried out through a participatory approach that included observation of the school’s organizational structure, analysis of the school’s vision and mission, and student involvement in co-curricular and extracurricular activities. The implementation results showed that students were able to prepare learning documents in accordance with the characteristics of SMAN 7 Mataram students, conduct guided teaching practice by utilizing feedback from mentor teachers, and design independent learning activities based on students’ interests. The conclusion of this activity affirms that PLP mentoring at SMAN 7 Mataram is effective in improving students’ readiness as prospective educators. The implications of this activity indicate the importance of strengthening initial communication between partner schools and teacher education institutions (LPTK), as well as utilizing school data by students to design learning that is more contextual, relevant, and aligned with learners’ needs.